Heart failure in systemic right ventricle: Mechanisms and therapeutic options - Sabbah, Belal Nedal; Arabi, Tarek Ziad; Shafqat, Areez; Abdul Rab, Saleha; Razak, Adhil; Albert-Brotons, Dimpna Calila (Frontiers in Cardiovascular Medicine, 2023)
d-loop transposition of the great arteries (d-TGA) and congenitally corrected transposition of the great arteries (cc-TGA) feature a right ventricle attempting to sustain the systemic circulation. A systemic right ventricle (sRV) cannot support cardiac output in the long run, eventually decompensating and causing heart failure. The burden of d-TGA patients with previous atrial switch repair and cc-TGA patients with heart failure will only increase in the coming years due to the aging adult congenital heart disease population and improvements in the management of advanced heart failure. Clinical data still lags behind in developing evidence-based guidelines for risk stratification and management of sRV patients, and clinical trials for heart failure in these patients are underrepresented. Recent studies have provided foundational data for the commencement of robust clinical trials in d-TGA and cc-TGA patients. Further insights into the multifactorial nature of sRV failure can only be provided by the results of such studies. This review discusses the mechanisms of heart failure in sRV patients with biventricular circulation and how these mediators may be targeted clinically to alleviate sRV failure.